Seeds of change the story of cultural exchange after 1492 - Hawke, Sharryl; Davis, James Edwin 1940-.; National Museum of Natural History (U.S.).; National Council for the Social Studies (New York Addison-Wesley Pub., 1992)
Presents the different contributions made to the New World by European explorers and settlers and the effects these contributions had on American history and cultural life.
"A joint project of the National Museum of Natural History, Smithsonian Institution, and the National Council for the Social Studies."
Based on the exhibit at the National Museum of Natural History in Washington, D.C.
Keywords: Cultural relations -- History -- Exhibitions; Culture diffusion -- History -- America -- Exhibitions; America -- History -- To 1810 -- Exhibitions